The Influence of Social Media on Adolescent Attitudes at State Senior High School 10 Pekanbaru - Redho, Ahmad; Meliza, Meliza; Yanti, Rifa (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Adolescence is a phase between childhood and Adulthood between the ages of 10 and 19. Social network usage in Indonesia reaches 3 hours and 18 minutes a day. That period is the best in the world. Excessive use of social media can affect many factors, one of which is the attitude of adolescents. This study aims to determine the impact of social media on Adolescent Attitudes at SMA Negeri 10 Pekanbaru. Used in this type of research a quantitative method with a correlational Research Approach using online questionnaire distribution through G-From samples This study uses the slovin method obtained a sample of 263 Selecting people and samples technique used stratified Random sample, and statistical testing using the Chi-square test. The results of the study were shown that the majority Social Network use was high, amounting to 141 (53.6) respondents, the majority of attitudes tended to be negative, namely 167 (63.5%) based on the results of the Chi-Square test The Influence of social media on Adolescent Attitudes at SMA Negeri 10 Pekanbaru obtained P-Value <0.05 (0.000). It can be concluded that social networks have an impact on the Attitudes of Adolescents at SMA Negeri 10 Pekanbaru. It is expected that the teaching staff at SMA Negeri 10 Pekanbaru can control and provide understanding to students not to use social media excessively